Preparation of Plant-based Insecticide Chamaejasmin Soluble Liquid and Its Biological Activity against Aphis craccivora and Pieris rapae - Tang, Xiaorong; Chen, Shaoling; Hou, Taiping (Asian Journal of Chemistry, 2010)
Chamaejasmin is the mixture of many natural insecticidal ingredients from the ethanol extract of components. Chamaejasmin soluble liquid was prepared and its insecticidal activity against Aphis craccivora and Pieris rapae and its stability were evaluated. Results showed that it had good insecticidal activity and good stability. Its median lethal concentration (LC50) values (24 h after treatment) against Aphis craccivora and Pieris rapae were 26.9 and 38.6 mg L-1, respectively. The results of analysis of variance (ANOVA) indicated that after the prepared soluble liquid was stored at 54 ± 2 °C for 14 d or at room temperature for 12 months, its insecticidal activity had no significant change. The content of 1,5-diphenyl-1-pentanone in the soluble liquid was 0.39 %.